INNA N. GOLUBOVSKAYA AS THE FOUNDER OF A UNIQUE COLLECTION OF MEIOTIC GENE MUTATIONS IN MAIZE AND A TALENTED RESEARCHER OF THE PROBLEM OF MEIOSIS GENETIC CONTROL - Yu. F. Bogdanov (Труды по прикладной ботанике, генетике и селекции)
Over 40 years, Inna Nikitichna Golubovskaya studied the fundamental problem of genetic control of meiosis, using meiosis in Zea mays as the model. She discovered more than half of 50 genes and gene alleles controlling meiosis in maize anthers and ovules, and studied even more of them. Having started with her researches at the Institute of Cytology and Genetics, Siberian Branch of the USSR Academy of Sciences (Novosibirsk) in 1972, she moved in 1986 to the N. I. Vavilov Institute of Plant Industry (Leningrad/St. Petersburg) to become the leader of a research group. In 1993, she started to collaborate with the Department of Biology, University of North Dakota (USA). There she worked during the field seasons until 1998. In 1999, Dr. Golubovskaya was invited to work with the Department of Cell and Molecular Biology, California State University at Berkeley. She developed and maintained a seed collection of genetic maize lines bearing mutations of meiotic genes, and in 2012 brought it to the Vavilov Institute. She was actively involved in cloning and studying major genes regulating meiosis in maize at the molecular level, and their expression in meiotic process. I. N. Golubovskaya’s contribution to the studies on maize genetics and genetic control of meiosis was expressly extolled by American geneticists.